The Genetic Makeup and Expression of the Glycolytic and Fermentative Pathways Are Highly Conserved Within the Saccharomyces Genus - Boonekamp, Francine J.; Dashko, Sofia; van den Broek, Marcel; Gehrmann, Thies; Daran, Jean-Marc; Daran-Lapujade, Pascale (Frontiers in Genetics, 2018)
The ability of the yeast Saccharomyces cerevisiae to convert glucose, even in the presence of oxygen, via glycolysis and the fermentative pathway to ethanol has played an important role in its domestication. Despite the extensive knowledge on these pathways in S. cerevisiae, relatively little is known about their genetic makeup in other industrially-relevant Saccharomyces yeast species. In this study we explore the diversity of the glycolytic and fermentative pathways within the Saccharomyces genus using S. cerevisiae, S. kudriavzevii and S. eubayanus as paradigms. Sequencing data revealed a highly conserved genetic makeup of the glycolytic and fermentative pathways in the three species in terms of number of paralogous genes. Although promoter regions were less conserved between the three species as compared to coding sequences, binding sites for Rap1, Gcr1 and Abf1, main transcriptional regulators of glycolytic and fermentative genes, were highly conserved. Transcriptome profiling of these three strains grown in aerobic batch cultivation in chemically defined medium with glucose as carbon source, revealed a remarkably similar expression of the glycolytic and fermentative genes across species, and the conserved classification of genes into major and minor paralogs. Furthermore, transplantation of the promoters of major paralogs of S. kudriavzevii and S. eubayanus into S. cerevisiae demonstrated not only the transferability of these promoters, but also the similarity of their strength and response to various environmental stimuli. The relatively low homology of S. kudriavzevii and S. eubayanus promoters to their S. cerevisiae relatives makes them very attractive alternatives for strain construction in S. cerevisiae, thereby expanding S. cerevisiae molecular toolbox.